'Public Theology' in Luke-Acts: The Witness of the Gospel to Powers and Authorities. (29th February 2016) - Edwards, James R.
Abstract : This study surveys the numerous and diverse powers and authorities to which the gospel is addressed in Luke-Acts, including major Jewish institutions and officials, Herodian rulers, Roman military officers, Greco-Roman officials, diverse officials, and pagan cults and supernatural powers. Well over half the references to authorities in Luke-Acts occur nowhere else in the New Testament. The frequent and diverse references to powers defend Christianity in a preliminary and obvious way from charges of political sedition. In a broader and more important way, however, they redefine power itself according to the standard of the gospel.